Correlation of TTF-1 immunoexpression and EGFR mutation spectrum in non–small cell lung carcinoma - Tripti Nakra; Varsha Singh; Aruna Nambirajan; Prabhat Singh Malik; Anant Mohan; Deepali Jain (Journal of Pathology and Translational Medicine, 2021)
Background Thyroid transcription factor (TTF-1) is a diagnostic marker expressed in 75%–85% of primary lung adenocarcinomas (ACs). Activating mutations in the tyrosine kinase domain of the epidermal growth factor receptor (EGFR) gene is the most common targetable driver alteration in lung AC. Previous studies have shown a positive correlation between TTF-1 and EGFR mutation status. We aimed to determine the predictive value of TTF-1 immunoexpression for underlying EGFR mutation status in a large Indian cohort. Methods This retrospective designed study was conducted with medical record data from 2011 to 2020. All cases of primary lung AC and non–small cell lung carcinoma not otherwise specified (NSCLC, NOS) with known TTF-1 expression diagnosed by immunohistochemistry using 8G7G3/1 antibodies and EGFR mutation status diagnosed by quantitative polymerase chain reaction were retrieved, reviewed, and theresults were analyzed. Results Among 909 patient samples diagnosed as lung AC and NSCLC, NOS, TTF-1 was positive in 76.8% cases (698/909) and EGFR mutations were detected in 29.6% (269/909). A strong positive correlation was present between TTF-1 positivity and EGFR mutation status (odds ratio, 3.61; p < .001), with TTF-1 positivity showing high sensitivity (90%) and negative predictive value (87%) for EGFR mutation. TTF-1 immunoexpression did not show significant correlation with uncommon/dual EGFR mutations (odds ratio, 1.69; p = .098). EGFR–tyrosine kinase inhibitor therapy was significantly superior to chemotherapy among EGFR mutant cases irrespective of TTF-1 status; however, no significant differences among survival outcomes were observed. Conclusions Our study confirms a strong positive correlation between TTF-1 expression and common EGFR mutations (exon 19 deletion and exon 21 L858R) in advanced lung AC with significantly high negative predictive value of TTF-1 for EGFR mutations.